2018
DOI: 10.31941/jurnalpena.v32i2.805
|View full text |Cite
|
Sign up to set email alerts
|

PENATALAKSANAAN FISIOTERAPI KONDISI FROZEN SHOULDER e.c TENDINITIS MUSCLE ROTATOR CUFF DENGAN MODALITAS SHORT WAVE DIATHERMY, ACTIVE RESISTED EXERCISE DAN CODMAN PENDULAR EXERCISE

Abstract: <p><strong>Background: </strong>Frozen shoulder is a pain in shoulders which conduces limitedness of shoulder joint motion. Tendinitis in M.Rotator Cuff, is an inflammation occured in  muscle tendons fused in Rotator Cuff. Physiotherapy problematics of Frozen Shoulder are the existence of pain, the limitedness of joint motion, the decline of muscle strength, and the interference of functional activity. Physiotherapy examination includes examining pain with Verbal Descriptive Scale (VDS), exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…Research conducted by Putri (2018) states that providing active resistance exercises combined with modalities can reduce shoulder pain and increase the shoulder joint's range of motion with a frozen shoulder diagnosis. In addition, active resisted exercise given to patients with weak shoulder muscles shows that active resisted exercise can increase muscle strength in patients with frozen shoulders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research conducted by Putri (2018) states that providing active resistance exercises combined with modalities can reduce shoulder pain and increase the shoulder joint's range of motion with a frozen shoulder diagnosis. In addition, active resisted exercise given to patients with weak shoulder muscles shows that active resisted exercise can increase muscle strength in patients with frozen shoulders.…”
Section: Discussionmentioning
confidence: 99%
“…In 40 cases, Hawkins et al discovered an average one-year delay in diagnosis, with only 30% identified within six weeks of damage. 7 Bankart lesions are shoulder injuries that are commonly caused by sports activities. 8 Shoulder dislocations can occur from trauma or hyperactivity (genetic or laxity of the capsule and ligaments).…”
Section: Interventionsmentioning
confidence: 99%
“…Kombinasi dari ketiga latihan ini bertujuan untuk mencegah perlengketan pada sendi bahu dengan melakukan gerakan pasif sedini mungkin yang dilakukan oleh pasien secara aktif dan diberikan beban. Tujuan lain dari ketiga latihan tersebut untuk mengulur struktur jaringan lunak seperti otot dan tendon sehingga mengakibatkan fleksibilitas jaringan tersebut dapat terjaga sehingga terjadi peningkatan lingkup gerak sendi bahu dan secara otomatis akan meningkatkan aktifitas fungsionalnya (Putri & Irine, 2018). Oleh http://jurnal.unissula.ac.id/index.php/abdimasku DOI: http://dx.doi.org/10.30659/abdimasku.2.1.16- 2218 || Jurnal ABDIMAS-KU: Jurnal Pengabdian Masyarakat Kesehatan Unissula karena itu peneliti melakukan penyuluhan kepada komunitas lansia melalui program edukasi dan penerapan terapi latihan untuk mencegah dan mengatasi nyeri bahu pada Lansia di Posyandu Lansia RW 2 Kelurahan Pandanwangi Malang.…”
Section: Pendahuluanunclassified
“…Latihan-latihan tersebut diaplikasin dengan tujuan e-ISSN: 2963-5268;p-ISSN: 2963-5039, Hal 36-44 untuk mengurangi perklengketan dan tekanan pada jaringan-jaringan area bahu. Selain itu, Latihan yang digunakan pada bahu juga dapat meningkatkan fleksibilitas jaringan sehingga lingkup gerak sendi bahu akan semakin meningkat (Putri & Irine, 2018).…”
unclassified